2014
DOI: 10.1039/c4ra07512a
|View full text |Cite
|
Sign up to set email alerts
|

Highly concentrated MoS2 nanosheets in water achieved by thioglycolic acid as stabilizer and used as biomarkers

Abstract: Synthesis of water soluble MoS2 quantum dots from the monolayer nanosheets of MoS2, using thioglycolic acid (TGA) was reported in this study. TGA molecules not only exfoliated the bulk of MoS2, but also modified the hydrophobic surface of MoS2 with hydrophilic carboxylic acid groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…The gap between the frequencies of these two phonon modes depends upon the method of exfoliation, a close gap shows that monolayer structure is more prominent. Frequency of the E 1 2g mode decreases and A 1g mode increases, when number of layers of MoS 2 are increased [43,44].…”
Section: Resultsmentioning
confidence: 98%
“…The gap between the frequencies of these two phonon modes depends upon the method of exfoliation, a close gap shows that monolayer structure is more prominent. Frequency of the E 1 2g mode decreases and A 1g mode increases, when number of layers of MoS 2 are increased [43,44].…”
Section: Resultsmentioning
confidence: 98%
“…Ac omparison of the DRIFT spectra of cysteine with Cys-2H-MoS 2 showed that the vibrational properties of the cysteine on the 2H-MoS 2 surface have been altered considerably through reaction with 2H-MoS 2 .F irstly,inc ysteine af eature at 2532 cm À1 attributed to the n SÀH was observed. [27][28][29][30][31][32][33][34][35] Secondly,c ysteine displayed broad features at 1745 and 1377 cm À1 corresponding to stretches of its carbox- This would suggest that the thiol group of cysteine had reacted in the presence of 2H-MoS 2 .All previous reports on the reaction between organic thiols and MoS 2 showed as imilar loss of the n SÀH by IR spectroscopy,l eading to the conclusion that the thiol had reacted with the MoS 2 .…”
mentioning
confidence: 78%
“…Pristine 2H-MoS 2 did not disperse in water ( Figure S6), and few methods to effectively disperse 2H-MoS 2 in water by functionalization exist. [30,46] Importantly,the aqueous Cys-2H-MoS 2 dispersions were stable for at least one week. Furthermore,wecould vary the pH of the aqueous dispersions,w ith no effect on the dispersability of the Cys-2H-MoS 2 ( Figure S6).…”
Section: Angewandte Chemiementioning
confidence: 98%
See 1 more Smart Citation
“…Bulk TMDs are semiconductors with an intrinsic band-gap and exhibit noteworthy optical and electronic properties desirable for energy conversion and storage, [1][2][3][4][5][6][7] sensing, [8][9][10] and photodynamic/ photothermal therapy. [11][12][13] Analogously to graphite, numerous van der Waals forces keep together the layered sheets of TMDs forming stacks. However, despite their close similarity to graphene, TMDs offer significant advantages related to their band-gap dependent electronic properties, 14,15 which can be tuned by altering the transition metal and/or the chalcogen composition.…”
Section: Introductionmentioning
confidence: 99%